2019
DOI: 10.1002/aur.2075
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of vocalization change in children with autism receiving early intervention

Abstract: Children with autism spectrum disorder (ASD) commonly present with comorbid language impairment, negatively impacting their learning and participation across settings. Addressing these needs requires a detailed understanding of their communication trajectories. In this study, we used the language environment and analysis (LENA) system to examine possible changes in children's (a) vocalizations and (b) ratio of speech to nonspeech vocalizations over a 10-month period. Data for 23 children with ASD (17M, 6F; age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Although these findings align with prior research related to the language development of children with ASD (Trembath et al, 2019), it is important to note that correlations were only observed between gestures and total communication score and children’s severity of autism symptoms. No significant correlations were found for the other key skills or between the ECI and children’s cognitive ability or gender.…”
Section: Discussionsupporting
confidence: 88%
“…Although these findings align with prior research related to the language development of children with ASD (Trembath et al, 2019), it is important to note that correlations were only observed between gestures and total communication score and children’s severity of autism symptoms. No significant correlations were found for the other key skills or between the ECI and children’s cognitive ability or gender.…”
Section: Discussionsupporting
confidence: 88%
“…Phonetic inventory-the number of different speech sounds produced-is a core aspect of structural language development in children but impaired in at least some children on the autism spectrum (Saul & Norbury, 2020;Yoder et al, 2015). The ratio of speech to non-speech vocalizations was selected on the conceptual basis that it reflects children's capacity to produce intelligible-and thus easily interpreted-communicative acts, and emerging evidence of a possible association with greater language development among children receiving intervention (e.g., Plumb & Wetherby, 2013;Trembath et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While a number of authors have identified the potential for LENA to act as a sensitive measure of vocal change in children with ASD, including those who are minimally verbal, there is growing evidence of challenges with reliability and validity, particularly in children with echolalia and in older children approaching (and certainly beyond) the designated age range of 0 to 5 years [33][34][35].…”
Section: Technology In the Assessment Of Children With Asd At The Prelinguistic Stage Of Communication Developmentmentioning
confidence: 99%